Identification of WTAP-related genes by weighted gene co-expression network analysis in ovarian cancer - Jing Wang; Jing Xu; Ke Li; Yunke Huang; Yilin Dai; Congjian Xu; Yu Kang (BMC, 2020)
Abstract Background Wilms tumor 1 associated protein (WTAP) modulates other genes via transcriptional and post-transcriptional regulation, in particular, by acting as a N6-methyladenosine writer or binding to the 3'UTR of mRNA, and promotes a variety of tumuors. However, the roles and mechanisms of WTAP in ovarian cancer are unknown. Results In this study, using univariate Cox analysis and online CPTA analysis, we found that WTAP was a poor prognostic factor for ovarian cancer, and its protein expression level was higher in ovarian cancer than in normal tissue. Functionally, WTAP promoted the proliferation, invasion, and migration capability of ovarian cancer, according to the results of real time cellular analysis (RTCA), EdU cell proliferation assay, transwell assay. Subsequently, we identified a module containing 133 genes that were carefully related to WTAP expression through weighted gene co-expression network analysis (WGCNA). By calculating the hazard ratios of these genes and comparing their differences in the WTAP high-expression group and the low-expression group, we observed that there was a significant positive correlation between WTAP and two poor survival-related genes, family with sequence similarity 76 member A (FAM76A) and HBS1 like translational GTPase (HBS1L), which was also verified by quantitative real-time PCR in SKOV3 and A2780 cells. Conclusion WTAP functions as an oncogenic factor that promotes the progression of ovarian cancer in which WTAP-HBS1L/FAM76A axis may be involved. Our study indicates the potential role of WTAP in prognostic biomarker and therapeutic target for ovarian cancer.